Regulation of lung immunity by dendritic cells: Implications for asthma, chronic obstructive pulmonary disease and infectious disease. Issue 6 (August 2019) - Peters, Marcus; Peters, Karin; Bufe, Albrecht
Since the first description of dendritic cells by Steinman and Cohn in 1973, this important cell type has gained increasing attention. Over 4000 papers have been published on this topic annually during the last few years. At the beginning, dendritic cells were recognized for their immune stimulatory properties and their importance in initiating an adaptive immune response. Later, it was found that dendritic cells do not only initiate but also regulate immune responses. This attribute makes the so-called regulatory dendritic cells highly important for the prevention of exaggerated immune responses. Immune cells make contact with different Ags every day and must be tightly controlled to prevent excessive inflammation and subsequent organ destruction, particularly in organs such as the gut and lungs. Here, we give a brief overview of our current knowledge on how immune responses are controlled by dendritic cells, highlighting how they are involved in the induction of peripheral tolerance. We focus on what is known about these processes in the lung, with a closer look at their role in the induction and control of diseases such as bronchial asthma, chronic obstructive pulmonary disease and lung infections. Finally, we summarize some current approaches to modulate the behavior of dendritic cells that may hopefully lead to future therapeutics to control exaggerated immune responses.